Pubertal timing as an indicator of early life stress in Roman Italy and Roman Gaul. Issue 3 (30th December 2022) - Avery, L. Creighton; Prowse, Tracy L.; Findlay, Sheri; de Seréville‐Niel, Cécile Chapelain; Brickley, Megan B.
Abstract: Objectives: Puberty is a period of rapid growth and development, and the age of onset and duration of puberty may serve as an indicator of developmental stress during childhood. In this study, we compare pubertal timing and tempo in individuals from two Roman Imperial cemetery sites, integrating biological and social factors to better understand pubertal timing differences and their possible connection to Early Life Stress (ELS) and peri‐pubertal stress. Materials and Methods: Osteological methods to estimate pubertal timing were applied to 264 individuals from Lisieux‐Michelet (4th–5th centuries CE; France) and Isola Sacra (1st–4th centuries CE; Italy). Peptide analysis of tooth enamel was used to assess sex in a sub‐sample of pre‐pubertal remains. Results: Individuals experienced puberty between 9 and 20 years of age, with females experiencing the acceleration stage earlier than males ( p < 0.05, g > 1.2). Between the two sites, no significant differences were noted for age‐at‐death during acceleration, peak height velocity, and deceleration (i.e., the active stages of puberty). Menarche occurred around 15 years of age. Discussion: The inter‐site comparisons demonstrate similar patterns of pubertal timing and tempo. For males, the pubertal timing aligns with ancient literary descriptions of key puberty milestones. Females entered puberty earlier than literary sources suggest and experienced puberty for an extended period, pointing to possible gendered exposure to ELS and peri‐pubertal stress, influenced by their social status in the Roman Empire. These results demonstrate how pubertal timing and tempo can be used to infer developmental stress in past populations.